Adopted Children in the Perspective of National Law and Islamic Law in Indonesia - Hasbi Umar; Husin Bafadhal; Arnelli Darwita (International Journal Labs, 2023)
Adoption or adoption of children is clearly regulated in Islamic law where an adopted child remains devoted to his biological parents while adoptive parents are only obliged to maintain, educate the adopted child until the adopted child can be independent and between the adopted child and the adoptive family do not inherit each other and also applies the law on mahrom so that between adopted children and family must not be seen with each other, The adoptive father must not be the marital guardian of his adopted child if the adopted daughter is to marry. The arrangement of adopted children for non-Muslims in Indonesia is based on civil law provisions where between adopted children and adoptive families and children are considered as biological children as if adopted children were born from the womb of their adoptive mothers and inherit each other.